Slab lined pits at Veines - Westgaard, Heidi Fløttum; Niemi, Anja Roth; Henriksen, Jørn Erik (Tromura, 2026)
In 2022, the Arctic University Museum of Norway investigated a site with a possible Sami farm settlement and four slab lined pits. Large quantities of whale bones, originating from a single right whale, were found close to the pits. The dates range from about 100 AD to about the end of the 9th century. The oldest dates are possibly attributed to the use of old wood from driftwood. Three of the four pits have dates to the latter half of the 6th century, of which one of these pits appears to have been reused in the first half of the 7th century. The last pit has been dated to use throughout the 9th century. A possible scenario is that three of the pits were established in the latter half of the 6th century for the exploitation of a whale that stranded here or nearby. The pits may then have been reused and supplemented, for later exploitation of other animals to produce marine oils.A hearth, path, roadbed and stone fence were documented in connection with the presumed Sami farm settlement. Beyond this, no unambiguous findings were made that shed light on the character and time depth of the settlement, other than that the area has been in use to this day.
Keywords: slab lined pits; marine oils; production; whale; whale bone; iron age; hearth; sami; sami settlement